THE STRESS-AND-STRAIN STATE OF THE SOUTH-EASTERN PART OF THE SKYBA AND BORYSLAV-POKUTTYA NAPPES OF THE UKRAINIAN CARPATHIANS - I. M. Bubniak; Yu. M. Vikhot; M. V. Nakapelyukh (Геодинамика и тектонофизика)
The article presents results of field studies and interpretation of tectonophysical data from profiles in the valleys of Bystritsa Nadvornyanskaya, Prut, Pistynka (the right-side tributary of the Prut river), Belyi and Chernyi Cheremosh, and Seret rivers. The stress fields reconstructed from different groups of joints and slickensides in flysch and molasse sediments of the Skyba and Boryslav-Pokuttya nappes are analyzed.A combination of the structural-paragenesis and kinematic analysis methods provided for determination of deformation modes, their sequences, and  average azimuth values of orientations of the principal axes of regional paleostress fields (σ1, σ2, σ3) which were manifested through the Alpine stage of the Ukrainian Carpathians development.The paleostress fields were reconstructed for the south-eastern part of the Skyba nappe of the Ukrainian Carpathians and the Boryslav-Pokuttya nappe of the Carpathian foretrough. The article describes similarities and differences in the stress-and-strain states, specific features of the paleostress fields, and the ratio of joints in different groups (oblique and perpendicular to the rock layers) and slickensides in the area under study.